A Study on Slot Design of Motorcycle Windshield to Improve Aerodynamics Features - Muhammad Izzat Nor, Ma'arof; Tang, Peng Rhu; Rizal Effendy, Mohd Nasir; Hazran, Husain; Girma, Tadesse Chala (INTI International University, 2019)
In motorcycle competitions, aerodynamics plays a fundamental role. In order to improve the performance of racing motorbikes, various windshield designs have been studied experimentally. The objective of this study was to minimize the magnitude of skin-friction on a Ducati 1198SP track-motorcycle’s windshield via the integration of slots. An alpha prototype in the motorcycle windshield was designed for the Ducati 1198SP track-motorcycle, and validation was performed on the performance of the newly designed slot variation in the motorcycle windshield in term of aerodynamic features. The newly concept included a double layered windshield construction with the integration of slots, which was tested in a wind tunnel to compare its aerodynamics properties with a stock windshield design of the Ducati 1198SP track-motorcycle. It was proven via the experiment that the Concept I has successfully improved the aerodynamic performance when the tilted angle of the slotted design was at 3.9472°. The particular windshield had the lowest coefficient of drag, lift and the drag and lift force when it travels at 20 m/s. For future studies, more variations of the slot and double layer designs could be further tested.